ANALISIS IMPLEMENTASI ENVIRONMENTAL HEALTH AND SAFETY STANDARD BERDASARKAN AUN-QA (ASEAN UNIVERSITY NETWORKING QUALITY ASSURANCE) MANUAL (Studi Kasus pada Salah Satu Fakultas Kesehatan Masyarakat di Indonesia) - Afifah Listiarina; Ida Wahyuni; Siswi Jayanti (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
AUN-QA is an Southeast Asian international accreditation in order to emerge mision on higher education standard. One of them is measured byenvironmental health and safety standard criteria. In 2015, Public Health “X” already got accreditation by AUN-QA but since they have not reached highest rating so they should improve their rating, in particular on environmental health and safety standard criteria. This research was to analyze the implementation in Public Health “X” toward environmental health and safety standard according to AUN-QA Manual. The method of this research was descriptive qualitative research with in depth interview and observation. The subject on this research were five peoples as main informant and seven peoples as triangulan informant. Result showed that rating implementation percentages in Public Health “X” toward Occupational Safety and Health (OSH) policy, OSH planning programe, Personal Protective Equipment (PPE) management, fire extinguisher and first aid utilization and maintenance, evacuation route planning, and emergency response planning were 22,22%; 0%; 25%; 26,13%; 50%; 72,9%; 11,11%. With those each scale, that criteria also measured by AUN-QA scale which 3; 3; 4; 4; 5; 5; 2. The summary of the assessment review was 3,75 or between “Inadequate” and “Adequate”. University “X” have not made AUN-QA as their priority and guidance in facility and infrastructure guidance, in particular facilities and infrastructure that meet onenvironmental health and safety standard. Therefore, Public Health “X” have to work on progress to fulfill their criteria on OSH policy, OSH planning programe, Personal Protective Equipment (PPE) management, fire extinguisher and first aid utilization and maintenance, evacuation route planning, and emergency response planning according to national regulation in order to enhance highest rating on AUN-QA re-accreditation.